Disciplining the everyday state and society? Anti-corruption and Right to Information activism in Delhi. (October 2013) - Webb, Martin
This article explores attempts by anti-corruption and Right to Information activist groups in Delhi to discipline state–citizen interactions through the innovative application of legal mechanisms for bureaucratic transparency and accountability, in particular the Right to Information Act of 2005. Drawing on detailed ethnography, I show how activist strategies can achieve positive results in specific cases. However, a paradox emerges as, in the everyday practice of dealing with poor clients and government officials, activists have to accommodate and work through the very processes of mediation, personalisation and inequality based on social and cultural capitals which they identify as problematic in the functioning of the state. A focus on the everyday practice of anti-corruption activism provides an opportunity to look beyond the recent hubris concerning anti-corruption in India and develop a closer understanding of how projects to reform the state–citizen relationship actually play out on the ground.